Indian Timber Imports - an Analysis - Bansal, A. K. (Indian Forester, 2004)
India is one of the major users of wood in the Asia-Pacific region and till recently had the privilege of having abundance quantity of timber from several tropical hardwoods. Despite industrial and technological advancement for development of many new generation materials and products , wood continues to be an indispensable material for several economically vital end use applications. As .the domestic production of timber is not adequate to meet the growing demand imports are permitted under Open General License. This paper presents a trend analysis of timber imports into the country with respect to trade volumes , overall quality of available import data , countries from where imports are taking place and the import routes , and makes some futuristic suggestions.